Strong Scattering from Low-Frequency Rattling Modes Results in Low Thermal Conductivity in Antimonide Clathrate Compounds - Ciesielski, Kamil M.; Ortiz, Brenden R.; Gomes, Lidia C. [UNESP]; Meschke, Vanessa; Adamczyk, Jesse; Braden, Tara L.; Kaczorowski, Dariusz; Ertekin, Elif; Toberer, Eric S. (American Chemical Society (ACS), 2023)
Recent discoveries of materials with ultralow thermal conductivity open a pathway to significant developments in the field of thermoelectricity. Here, we conduct a comparative study of three chemically similar antimonides to establish the root causes of their extraordinarily low thermal conductivity (0.4-0.6 W m-1 K-1 at 525 K). The materials of interest are the unconventional type-XI clathrate K58Zn122Sb207, the tunnel compound K6.9Zn21Sb16, and the type-I clathrate K8Zn15.5Cu2.5Sb28 discovered herein. Calculations of the phonon dispersions show that the type-XI compound exhibits localized (i.e., rattling) phonon modes with unusually low frequencies that span the entire acoustic regime. In contrast, rattling in type I clathrate is observed only at higher frequencies, and no rattling modes are present in the tunnel structure. Modeling reveals that low-frequency rattling modes profoundly limit the acoustic scattering time; the scattering time of the type-XI clathrate is half that of the type-I clathrate and a quarter of that of the tunnel compound. For all three materials, the thermal conductivities are additionally suppressed by soft framework bonding that lowers the acoustic group velocities and structural complexity that leads to diffusonic character of the optical modes. Understanding the details of thermal transport in structurally complex materials will be crucial for developing the next generation of thermoelectrics.